Feasibility Study of Wind Energy Harvesting at TELCO Tower in Malaysia - Lim, Siow Chun; Meng, Tong Jia; Palanichamy, Chinnasamy; Eng, Gan Tian (International Journal of Energy Economics and Policy, 2019)
As the stride towards 5G intensifies in Malaysia, more Base Transceiver Stations (BTS) will be erected to fulfill the infrastructural needs. BTS tend to be built in isolated areas rendering tapping power from the main grid to be an economically unpleasant option. In Malaysia, the potential of wind energy as an energy source is largely untapped due to the relatively low average wind speed. However, BTS may not need a huge amount of power to function. Hence, this paper investigates the feasibility of application of small wind turbines (SWT) to fulfill the power needs of a typical BTS. The power consumption of a typical BTS would first be estimated followed by estimation of the power yield of few commercially available SWT's. Based on available wind data, it was found that the power generated from SWT is insufficient to match the power demand of a typical BTS. Keywords: Small Wind Turbine, Wind Energy, Base Transceiver Station JEL Classifications: Q42, Q47, Q56 DOI: https://doi.org/10.32479/ijeep.8106